Use of Antibiotics in Companion Animals from 133 German Practices from 2018 to 2023 - Roswitha Merle; Leonie Feuer; Katharina Frenzer; Jan-Lukas Plenio; Astrid Bethe; Nunzio Sarnino; Antina Lübke-Becker; Wolfgang Bäumer (Antibiotics)
Background/Objectives: While antibiotic usage in farm animals has been systematically monitored and reduced in many countries, including Germany, data on companion animals such as dogs and cats remain scarce. To address this gap, a study was conducted in Germany to analyze patterns of antibiotic use in dogs and cats. Methods: Antibiotic usage data were obtained from debevet, a cloud-based veterinary practice management software based in Berlin, Germany. Practices with fewer than 100 patients were excluded, and data from 2018 to 2022 were analyzed. Results: The analysis included 477,310 consultations of 78,381 dogs and 241,532 consultations of 55,729 cats across 133 veterinary practices. Antibiotics were used in 12.9% of dog consultations and 22.5% of cat consultations, with substantial variation across practices. Aminopenicillins, particularly amoxicillin, were the most commonly used antibiotics, while the highest-priority critically important antibiotics (HPCIAs) accounted for 12.4% of treatments. Follow-up treatments led to changes in antibiotic substances in 9.3% of cases, often within the first two days. Indications varied by species, with respiratory issues more frequent in cats and orthopedic problems in dogs. Body weight and breed characteristics influenced the likelihood of antibiotic treatment, with short-nosed breeds showing higher odds. Conclusions: The routine data analysis provided valuable insights into antibiotic use in dogs and cats, enabling tracking trends across species and indications over time. While some specific information was missing, the invoicing data’s completeness, the cost-effectiveness of their use, and their unbiased nature make them a robust tool for monitoring and informing legislative changes.